POLEMIK KEABSAHAN POLIGAMI: PERBANDINGAN HUKUM KELUARGA ISLAM INDONESIA DAN MALAYSIA - Husain Hasibuan, Badai; Asrona Warni Daulay, Dinda (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to compare the two legal systems that govern marriage in Indonesia and Malaysia. Indonesia uses Law Number 1 of 1974 concerning Marriage, while Malaysia implements the Federal Territory Islamic Family Law Act 1984. This study uses a qualitative method with a descriptive-analytical approach. A normative approach is applied in this study, focusing on the analysis of laws and regulations as a research object and primary data source. This study examines the polemic of determining the validity of polygamy based on differences in regulations between the two countries. The results of the study show that Indonesia and Malaysia have similarities in the principle of marriage, namely the principle of monogamy. Polygamy is allowed if the husband meets the conditions set out in the regulations of each country and obtains permission from the Religious Court (Indonesia) or Sharia Court (Malaysia). In addition, both countries place the permission of the first wife as the main prerequisite for filing a polygamy application. In Indonesia, the husband must apply for polygamy to the Religious Court which is then examined by a judge before being granted. In contrast, in Malaysia, a polygamy application in the Sharia Court begins with a request from the husband, which is then followed by the consent of the first wife. These findings strengthen the understanding of the similarities and differences in the application of Islamic family law in Indonesia and Malaysia, especially in the context of polygamy.